(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Development of seed is a complex physiological and molecular process that involves transport of nutrient, metabolic regulation, and expression of genes in a coordinated Significant progress has been made in understanding seed maturation, nutrient flow in developing seeds, and metabolism of storage compounds through physiological and genomic studies. Transport of sugar play a vital role in supplying carbon to seed and this mainly occurs through symplastic compartments within maternal and filial tissue. Molecular studies have also revealed the importance of gene regulation in seed development, including genomic imprinting and differential expression of maternal and paternal genes in the endosperm. In controlling autonomous endosperm development through mechanism involving DNA methylation and chromatin remodelling, Fertilization Independent Seed (FIS) genes play a vital role. Furthermore, carbohydrate and nitrogen metabolic pathways interact closely during seed maturation, influencing assimilate partitioning between starch and protein synthesis. Identification of nutrient sensing systems and signaling pathways involving sugars and nitrogen compounds will enhance understanding of seed development and may contribute to future crop improvement strategies.